Estudo da atividade cerebral na distonia focal idiopática utilizando ressonância magnética funcional - Faria, Danilo Donizete de [UNIFESP] (2020)
Introduction: Dystonia is a neurological syndrome characterized by sustained or intermittent involuntary muscle contractions, leading to repetitive twisting movements and / or abnormal postures with or without tremor. Focal dystonia may also be defined as a network disorder, previously attributed to the basal nuclei and currently to other areas such as the cerebellum, thalamus, and the sensorimotor cortex. Objective: To investigate the brain functional activity of individuals with idiopathic focal upper limb dystonia using finger tapping task functional magnetic resonance imaging. Methods: 27 right-handed patients and 26 controls, matched for sex and age underwent finger tapping task with the right hand, left and both hands interspersed with rest. The functional images were acquired with a 3.0 Tesla equipment (Siemens® PRISMA). Results: The number of finger taps was analyzed under the three conditions of interest. Patients had statistical significance fewer number of taps relative to controls for the right hand, and for both hands. There was no statistically significant difference for the left hand. Patients with focal upper limb dystonia showed a higher BOLD effect in the right cerebellum relative to controls during finger tapping with the right hand (509 voxels). No difference in terms of BOLD effect was found for the remaining conditions. The cerebellar cluster in which patients had a higher activity is ipsilateral to the affected limb, comprising lobes V and VI. Conclusion: This study corroborates the role of the distinct cerebellum activation between patients and controls. These data may form the basis to investigate cerebellar neuromodulation as a treatment strategy for this type of dystonia.